2010
DOI: 10.1161/circheartfailure.109.869438
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide Testing and the Accuracy of Heart Failure Diagnosis in the Emergency Department

Abstract: Background-It is often difficult to diagnose heart failure (HF) accurately in patients presenting with dyspnea to the emergency department (ED). This study assessed whether B-type natriuretic peptide (BNP) testing in these patients improved the accuracy of HF diagnosis. Methods and Results-Patients presenting to the Alfred and the Northern Hospital EDs with a chief complaint of dyspnea were enrolled prospectively from August 2005 to April 2007. Patients were randomly allocated to have BNP levels tested or not.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
(31 reference statements)
1
30
0
Order By: Relevance
“…In addition, it was reported that BNP does not reliably distinguish ARDS from AHFS [44]. In our study, the BNP level of patients with a history of heart failure who had dyspnea due to pulmonary disease or ARDS showed no significant difference compared to that of patients with acute dyspnea due to AHFS, a finding that is in agreement with prior reports [42,43]. Therefore, among patients with acute dyspnea (including those with a history of heart failure and those with ARDS), the baseline BNP level alone could have various limitations for making a differential diagnosis in the emergency setting, and further research is needed to address this issue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it was reported that BNP does not reliably distinguish ARDS from AHFS [44]. In our study, the BNP level of patients with a history of heart failure who had dyspnea due to pulmonary disease or ARDS showed no significant difference compared to that of patients with acute dyspnea due to AHFS, a finding that is in agreement with prior reports [42,43]. Therefore, among patients with acute dyspnea (including those with a history of heart failure and those with ARDS), the baseline BNP level alone could have various limitations for making a differential diagnosis in the emergency setting, and further research is needed to address this issue.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, BNP and N-terminal pro-BNP have been studied extensively and are frequently used in clinical practice. However, some recent randomized trials on the use of BNP to aid in diagnosis or serial BNP levels to dictate therapy in the acute setting found no improvement of diagnostic accuracy or important clinical outcomes because age, sex, and renal dysfunction have an impact on natriuretic peptide levels and need to be considered when test results are interpreted [42,43]. Also, patients with a history of decompensated HF can have chronically elevated BNP or N-terminal pro-BNP levels, making the test inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have not been able to provide bibliographical or manufacturer's data regarding the stability of MR-proANP under the storage conditions used: this important factor needs to be tested in future studies. Finally, questions may be raised regarding the degree to which biomarkers can improve clinical judgment in the diagnosis of acute heart failure: indeed, some studies have demonstrated that combining clinical evaluation with natriuretic peptide testing increases the probability of a correct diagnosis of CRD (10,12,13 ), whereas others were not able to show any significant improvement (39 ). However, we believe that an optimum use of natriuretic peptides can be achieved by considering, first, that they only form part of the diagnostic evaluation (15 ) and, second, that their thresholds can be adapted to the patient's characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies have indicated that the method of determining the clinical diagnosis and therefore its accuracy is fraught with difficulties (14). Furthermore, many of our study patients did not have a formal cardiologic and echocardiographic evaluation that has been used in many previous studies such as the one noted above (12).…”
Section: Discussionmentioning
confidence: 95%